2014
DOI: 10.1016/j.bbamem.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic variants of ganglio-tripod amphiphiles for membrane protein manipulation

Abstract: Membrane proteins operate in unique cellular environments. Once removed from their native context for the purification that is required for most types of structural or functional analyses, they are prone to denature if not properly stabilized by membrane mimetics. Detergent micelles have prominently been used to stabilize membrane proteins in aqueous environments as their amphipathic nature allows for shielding of the hydrophobic surfaces of these bio-macromolecules while supporting solubility and monodispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…In addition, as emerged from our TPA studies, the branched diglucoside group has better membrane protein stabilising properties. We previously observed that branched diglucoside‐bearing TPAs were superior to maltoside‐bearing TPAs for stabilising LHI–RC complexes 26a. A similar trend was observed for DCGs in the current study.…”
Section: Methodssupporting
confidence: 89%
“…In addition, as emerged from our TPA studies, the branched diglucoside group has better membrane protein stabilising properties. We previously observed that branched diglucoside‐bearing TPAs were superior to maltoside‐bearing TPAs for stabilising LHI–RC complexes 26a. A similar trend was observed for DCGs in the current study.…”
Section: Methodssupporting
confidence: 89%
“…Many novel agents have been developed over the past two decades, to address the narrow scope of utility of conventional detergents. These include small amphipathic agents such as tripod amphiphiles (TPAs),, glyco‐diosgenin (GDN), and hemifluorinated surfactants (HFSs), neopentyl glycol‐derived triglucosides (NDTs), medium‐sized peptide‐based amphiphiles (e.g., lipopeptide detergents (LPDs), short peptides and β‐peptides (BPs)) as well as large nanoassemblies such as amphipols (Apols),, nanodiscs (NDs) and nanolipodisqs . Facial amphiphiles (FAs) glucose or maltose neopentyl glycols (GNGs or MNGs) are particularly attractive because these agents have been highly successful in membrane protein structural study.…”
Section: Methodsmentioning
confidence: 99%
“…However, they have a number of disadvantages: they tend to form large protein-detergent complexes (PDCs), are often ineffective at efficiently extracting proteins from the membranes, and are often difficult to synthesize on a bulk scale. In contrast, small amphipathic agents have also been developed as exemplified by tripod amphiphiles (TPAs), 15 facial amphiphiles (FAs), 16 neopentyl glycol (NG) class amphiphiles (GNGs 17 or MNGs), 18 mannitol-based amphiphiles (MNAs), 19 neopentyl glycol triglucosides (NDTs), 20 and penta-saccharide amphiphiles (PSEs). 21 These can all be easily synthesized and are largely as effective as DDM at extracting proteins from the membrane.…”
Section: Introductionmentioning
confidence: 99%